Small Bowel Hamartoma: A Huge Diverticulum of Small Bowel - Hamdi Ebdewi; Amar M. Eltweri; Yahya Salama; Neshtman Gorgees; Leena Naidu; David J. Bowrey (Case Reports in Medicine)
A-20-year old male, with no significant medical history, presented with clinical features mimicking a perforated acute appendicitis. Because of features of peritonitis, a laparotomy was performed which showed a segment of small bowel with multiple large diverticula and mesenteric cysts. A segmental small bowel resection was performed. The patient made an uneventful recovery from surgery. Histology revealed features of a small bowel hamartoma.